2018
DOI: 10.12688/aasopenres.12837.1
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological assessment of sachet water “pure water” from five regions in Ghana

Abstract: Sachet water, popularly known as "pure water" has become an Background: invaluable entity in most Ghanaian households. Despite its importance, there is no extensive nationwide investigations on its wholesomeness for consumption. The aim of this study was to determine the microbiological quality of 41 brands of sachet water sampled in 16 districts across 5 regions in Ghana.The samples were analyzed for the presence of total and fecal Methods: coliform ( ) using the Colilert*-18 Test Kit. Escherichia coli Majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…This can be attributed to a sufficient amount of filtering, addition of chlorine, or faulty UV system testing, which may also contribute to the lack of bacterial pathogens in the sachet. A group researchers all reported contamination of sachet water sold in both Ghana and Nigeria with total coliforms in ranges different from the results reported by this study (Mosi et al, 2018;Tenebe et al, 2013;Owusu, 2016).…”
Section: Discussioncontrasting
confidence: 82%
“…This can be attributed to a sufficient amount of filtering, addition of chlorine, or faulty UV system testing, which may also contribute to the lack of bacterial pathogens in the sachet. A group researchers all reported contamination of sachet water sold in both Ghana and Nigeria with total coliforms in ranges different from the results reported by this study (Mosi et al, 2018;Tenebe et al, 2013;Owusu, 2016).…”
Section: Discussioncontrasting
confidence: 82%
“…with previous studies (Sheshe and Magashi, 2014;Mosi et al, 2018). The least value of 0.01mg/L phosphate was recorded in SB water while highest values of 1.15mg/L was recorded in EJ water (a value is slightly higher than the WHO recommended limit of 1.0mg/L), An increase in phosphate is indicative of the presence, of seepages from septic tank and run-offs.…”
Section: Igbinevbo I D; Akiri-obaroakpo T M; Ebun-igbeare Osupporting
confidence: 81%
“…13 This contamination of the water sources may be brought about by various activities including surface run off, animal and human faeces and urine. 14,15,16,17 This finding is in agreement with a study conducted by Raji et al, 18 in Sokoto State where the analyzed water sources were also found to be contaminated by bacteria of human and animal faeces was attributable to the fact that most wells are left open and not well sited as they are prone to contamination from various sources such as dumps and animal pen and with surface water which are prone to contamination mostly from human activities such as bathing and washing. All the water samples analyzed failed to meet WHO standards for drinking water because many potentially pathogenic bacteria were isolated in them, this corroborate the findings by Raji et al, 18 in Sokoto State, who reported that all the different water sources sampled had both total coliform count and fecal coliform count far above the WHO standards and as such the water was unfit for drinking purposes.…”
Section: Discussionmentioning
confidence: 99%